NUMERICAL ANALYSIS OF DROPLET DYNAMICS ON SLIT AND BARRIER SURFACE - Nur Azmar, Aldian
Interaction of fluid with solid surfaces involve interactions in the molecules that determine the behavior of the fluid when moving on the solid surface which is the contact area. When there is contact with a solid surface, the fluid can become wetting and non-wetting which is indicated by the large contact angle produced. In this study, multicomponent fluid dynamics through structures are investigated numerically using the Lattice Boltzmann Method or LBM. The structure used is in the form of gaps and barriers. The Shan–Chen model was applied to accommodate cohesion and adhesion interactions. To assess the ease with which the fluid passes through the structure, two quantities are calculated, namely the duration of the fluid passing through the structure and the volume fraction of fluid that is able to pass through the structure. To observe how these two quantities change, the fluid–solid interaction strength and Bond number are varied. Three different states are observed through variations in contact angle and Bond number, namely the droplet passes through the slit completely, the droplet passes through the slit but retains its volume fraction attached to the structure, and the fluid passes through the slit but attaches to the opposite side of the structure. From this study, it was found that the relationship between the contact angle is directly proportional to the length of time the fluid passes through the gap, the magnitude of the viscosity of the fluid also affects the rate of droplet to pass through the structure, namely the greater the viscosity of the fluid, the resulting time interval will be greater, but the magnitude of the viscosity ratio will be inversely time interval, as well as passing through the Bond equation is inversely proportional to the droplet structure of the rate.